Effects of modified tall oil and supplemental magnesium on growth performance, carcass characteristics, and meat quality of growing-finishing gilts - O'Quinn, P.R.; Woodworth, J.C.; Nelssen, Jim L.; Unruh, John A.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial was conducted to evaluate the effects of feeding modified tall oil (MTO) and supplemental magnesium (Mg) on growth performance, carcass characteristics, and meat quality of finishing gilts. No effect of treatment was observed on ADG, ADFI, or FIG during the growth trial. Feeding MTO reduced average backfat and increased intramuscular marbling, whereas supplemental Mg reduced first rib backfat (but not average backfat) and postmortem levels of glycogen in the longissimus muscle. Additionally, Mg altered whole blood metabolic profiles in a manner that should improve meat quality, although improvements in pH, drip loss, and color were not observed in this trial.
Keywords: Swine; Gilts; Modified tall oil; Magnesium; Meat quality